Polylactic Acid in Dentistry – A Sustainable Biomaterial for Oral Health and Clinical Practice - Musyt, Wiktoria; Dudziński, Szymon; Pietruszka, Wiktoria; Potrykus, Maria (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Polylactic acid (PLA) is a biodegradable, biocompatible polymer derived from renewable sources. In light of the growing importance of environmental sustainability, health promotion, and digital innovation, PLA has gained relevance in medical and dental sciences. The objective of this review is to explore PLA’s applications in dentistry while highlighting its potential role in patient safety, and the development of sustainable health solutions. Brief Description of the State of Knowledge: PLA is increasingly utilized in dental procedures due to its safety profile and compatibility with digital manufacturing technologies, including 3D printing. In surgery and periodontology, PLA-based membranes are used in guided bone and tissue regeneration (GBR/GTR). In prosthodontics, PLA supports the production of temporary crowns, bridges, and denture bases. In orthodontics, it is applied in palatal plates and aligners. Its biodegradable nature and absence of toxic residues make PLA a valuable alternative in preventive and environmentally conscious dental care. Summary: Although PLA shows strong potential, its mechanical limitations require further improvement. Research into composites and material modifications is ongoing. PLA represents a promising direction in dentistry, offering opportunities for innovation in clinical practice, sustainability, and the education of future healthcare professionals.